O consumo da dança em casas noturnas: alienação ou apropriação consciente? - Tortola, Eliane Regina Crestani (2011)
This research aims to understand the dance in leisure places, discussing if its use occurs alienated or conscious. So, it had focused on the analysis of dance as a product consumed in nightclubs, identifying how the industry works in the cultural corruption of meaning/significance of this manifestation by social actors who attend these urban spaces. The multi-placed ethnography (Marcus, 1998) was chosen for the investigation, because it considers the local knowledge distinctly probed, as identifying how the same phenomenon is perceived in different places and experienced by people with different desires and preferences. The investigative field was limited by a pilot project in 12 nightclubs in Maringá-PR, selecting five of them for the search, based on criteria such as: dance as the main attraction; different forms of dance; and diversity of public. Previous interviews with 15 patrons of houses were used, and by free observing and photographic registers as well to capture the necessary information, understanding that the conduct of research will promote people, things, the plot and the biography. The data show the alienated consumption of dance in nightclubs, which is much stronger because of the cultural industry, and for its corruption by social actors in order to satisfy their desires and needs. This reality has implications on the educational field, especially when they don't know or they ignore the attack about the subject by the media. That's why it is necessary to know for intervening, favoring the construction of a training process not different of the social actor, but close to him, which is mediating, intervening and emancipatory.